Transportation Control Model Of Medan Center Market - Herawati Simanjuntak, Sariguna; Tarigan, Johannes; Siagian, Morida (Jurnal Indonesia Sosial Sains, 2022)
Millions of Indonesians still supply their daily needs to a traditional market that is synonymous with the lower middle class. The study aimed at the problem of transportation at the center of the terrain city market and how to find solutions to the transport problem. The terrain city market center as a first-class market in the terrain city is one of the largest in the terrain city. One of the problems at the center of the terrain city market is that of transportation, which involves the daily congestion we encounter at a very critical stage. The central market for the city of Medan does seem to be physically, financially and under. In the study, problems are set in place (1) what is the current condition of the urban market and (2) what is the solution to the transportation problems that exist in the municipal market center? Using transportation control model approaches in the center of the city market that will be directly observed and analyzed using Vissim software. Researchers in this regard took a direct look at the problem at the city market center. Studies indicate that economic activity in the central urban market area has significant transportation problems, especially congestion. With the transport conditions and until the moment.